Culture of Individually Required Number of 2-Pronuclei-Stage Oocytes – Patient Participation in Decision-Making is in Accordance with the Aim of Avoiding Surplus Embryo Freezing - Cupisti, S.; Müller, A.; Hildebrandt, T.; Hackl, J.; Beckmann, M. W.; Dittrich, R. (Geburtshilfe und Frauenheilkunde, 2014)
Background: The aim of this study was to evaluate how many embryos will develop if more than 3 2-pronuclei-stage oocytes (2-PNOs) are cultured at the patientʼs request and in accordance with the Germany Embryo Protection Law.Methods: A total of 106 cycles of patients undergoing their 1st, 2nd or 3rd cycle of IVF or ICSI treatment in 2010 were prospectively included in the study. In each individual case, a decision was taken prior to treatment about the number of 2-PNOs to be cultured after each cycle.Results: Ninety female patients were treated for a total of 106 cycles. A mean of two to six 2-PNOs were cultivated for a period of between 3 and 6 days for each patient. After culture, no viable embryo was identified for 5 patients (4.7 %), a single viable embryo was identified for 37 cycles (34.7 %), and 2 viable embryos were identified for 52 cycles (48.8 %). Eleven patients (10.3 %) had 3 viable embryos after a further 11 cycles and 1 patient had 4 viable embryos in a single cycle. Ten of the patients with 3 embryos each opted to have all 3 embryos transferred in the same cycle. This meant that a single embryo from one patient with 3 viable embryos and a single embryo of the patient with 4 viable embryos were cryopreserved after culture. The pregnancy rate was 19 % per embryo transfer and 25 % per blastocyst transfer (20 pregnancies in total). All cryopreserved embryos were transferred in a subsequent cycle.Discussion: Based on this study it is possible to make a statement about the number of viable embryos which should be cultivated to obtain, at best, two embryos for transfer without running an unacceptably high risk of producing too many embryos which would then need to be cryopreserved. Only 12 patients (13.3 %) had more than 2 viable embryos. The number of supernumerary pre-implantation-stage embryos was acceptably low (only 2 patients had additional viable embryos, 2.2 %). This means that it is possible to fulfil the wishes of individual patients while complying with the German Embryo Protection Law.
Keywords: embryo; assisted reproductive technology (ART); ICSI; patient decision-making; Embryo Protection Law